Developing an Independence State: Some Insights from Qalam Publication - Rosman, Norziati Mohd (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2016)
This article is to identify a few concepts on independence and proposed a necessary approach in developing an identity of the country by analysing articles written in Qalam periodicals by three figures, Edrus, Dr Burhanuddin al-Helmy and Muhammad Isa Anshary. Qalam is a socio-politics periodical in Jawi script published in Singapore in 1950 until 1969. By analysing the writings, it is believed that proclamation of Indonesian independence in 1945 inspired the development of Malaysia as a sovereign country and influenced readers in Malaya, Singapore and Brunei in which their countries were still struggling for independence.